Kamlahari Movement in Nepal: Expanding Opportunities, Uncertain Achievements - Sapkota, Mahendra (Journal of Development Policy Research and Practice (JoDPRP), 2018)
This paper maps out a movement of Kamlahari girls in Nepal which is popularly known as ‘Kamlahari’ both in lingual and literal terms. This study analyses a semi-bonded child labour system among the girls of the Tharu ethnic community. Despite the long historical background of the Tharu movement, critics suggest that the freedom of Kamlahari in 2013 is largely neglected and has become a less prioritised agenda. Building on this critique, the paper aims to analyse different issues, challenges and opportunities of and from the Kamlahari movement, particularly in context of the western Tarai region of Nepal. Methodologically, the paper follows a set of qualitative methods, including narrative analysis of both primary and secondary sources. The central proposition of the paper is that there are some critical issues and contestations in the movement of Kamlahari girls, ranging from rescue and rehabilitation to educational support and livelihood sustenance. With the changing socioeconomic and constitutional provisions, Kamlaharies have had a number of opportunities for their mainstreaming, but there have been some uncertainties to benefit from them both at the level of policies and programmes. To emphasise this dilemma, the paper argues that ‘freedom of the Kamlahari girls’ is yet to be institutionalised at the grassroots level through a set of policy inputs and livelihood outcomes. The scope of this article is related to the following SDG / SDGs.